The Effect of Earnings-Related Benefits on Financial Work Incentives - Roantree, Barra (My University, 2024)
In most European Union countries, there is a link between the level of payment provided to those who have lost their job and the level of earnings in that job, at least for an initial period. While this provides valuable insurance to those who lose their job, a stronger link between unemployment benefits and previous earnings can exacerbate the moral hazard created by unemployment insurance. We examine strengthening this link for unemployment benefits in Ireland using SWITCH – a tax and welfare microsimulation model for Ireland – to simulate the financial work incentive impact of a proposed reform to current unemployment benefit policy. We find that implementing an earnings- related unemployment’s benefit leads to reduced short-term incentives to work for all those currently in employment, with the impact being greater for full-time employees.
PUBLISHED
Keywords: work incentives, earning- related benefits, unemployment benefits; Inclusive Society; WELFARE; income inequality